Analisis Sentimen Review Hotel Menggunakan Metode Naïve Bayes pada Hotel di Wilayah Kota Cirebon - Muhamad Jihad Andiana; Martanto Martanto; Umi Hayati (Universitas Wahid Hasyim, 2024)
Cirebon, a city in West Java, Indonesia, is known for its various tourist attractions, including culinary and historical sites. However, finding the right accommodation can be a challenge. To address this issue, a study has analyzed 875 hotel reviews in Cirebon from Google Maps, using the Naive Bayes method and the TF-IDF algorithm. The aim of this study is to help tourists get a better picture in choosing a hotel. The results show that this algorithm successfully achieved an accuracy of 90.52% in identifying whether the review was positive or negative. Even without the use of the SMOTE operator, the accuracy remains high, at 75.66%. So, this study provides a data-based solution for choosing a hotel in Cirebon.